Superhydrophobic fluorine-modified cerium-doped mesoporous carbon as an efficient catalytic platform for photo-degradation of organic pollutants. (June 2019) - Suresh, S.P.; Lekshmi, G.S.; Kirupha, S.D.; Ariraman, M.; Bazaka, O.; Levchenko, I.; Bazaka, K.; Mandhakini, M.
Abstract: Accumulation of hazardous waste from effluents of textile, medical, plastic and other industries in the water bodies present a serious threat to human health and environment. A major class of pollutants released from textile industrial wastewater, organic dyes lead to aesthetic pollution of environment, yet their decomposition is a non-trivial and energy-consuming task, while their degradation products may be carcinogenic. Here, we report on the a relatively simple synthesis of a super-hydrophobic platform for efficient, energy-undemanding visible light photocatalytic degradation of organic dyes. Fluorine-modified cerium-doped titania-loaded mesoporous carbon was synthesized using hydrothermal method on mesoporous silica as a low-cost template, and titaniun tetraisopropoxide and cerium nitrate as precursors. Scanning electron microscopy and X-ray diffraction analyses showed the presence of anatase phase of titania and the amorphous graphitic structure of the synthesized mesoporous carbon. From the Brunauer–Emmett–Teller analysis, surface area of the mesoporous carbon was calculated to be 1410 m 2 /g and from Barrett-Joyner-Halenda analysis, specific pore diameter was calculated as 0.7763 cm 3 /g. The ultraviolet diffuse reflectance spectroscopy showed that carbon and Ce species were responsible for the visible light response, and Tauc plot showed that the bandgap energy of titania decreased gradually from 2.5 to 1.93 eV due to Ce doping. The ultraviolet–visible spectroscopy, as well as direct experiments in dye degradation have demonstrated that the cerium-doped titania-loaded and fluorine-modified cerium-doped titania-loaded mesoporous carbons have good photocatalytic dye degradation activity in visible light, with the efficiency reaching impressive 96.7%. Graphical abstract: Image 1